Synthesis, Characterization, and Structural Comparisons of the First Neodymium(III) Sulfite‐Acetate Crystal Structure. Issue 1 (25th November 2018) - Dovgan, Jakob T.; Polinski, Matthew J.; Villa, Eric M.
Abstract : The first lanthanide sulfite compound with a secondary ligand, Nd(SO3 )(C2 H3 O2 ), was hydrothermally synthesized and solved with single‐crystal X‐ray diffraction. In order to prevent the facile oxidation of the sulfite to sulfate, careful control of both pH and reaction temperature were required for successful synthesis of the title compound; even slight changes in conditions allow for the facile oxidation of sulfite to sulfate and yields the known [Nd(C2 H3 O2 )(SO4 )(H2 O)2 ] structure. This two‐dimensional sheet topology further expands the chemistry of lanthanide sulfite extended structures and also allows for easy structural comparisons to other lanthanide sulfite compounds and the above mentioned neodymium sulfate‐acetate compound. Abstract :